Inhibitors of Selected Bacterial Metalloenzymes - Žalubovskis, Raivis; Winum, Jean-Yves (Current Medicinal Chemistry, 2019)
The utilization of bacterial metalloenzymes, especially ones not having mammalian (human) counterparts, has drawn attention to develop novel antibacterial agents to overcome drug resistance and especially multidrug resistance. In this review, we focus on the recent achievements on the development of inhibitors of bacterial enzymes peptide deformylase (PDF), metallo-β-lactamase (MBL), methionine aminopeptidase (MetAP) and UDP-3-O-acyl- N-acetylglucosamine deacetylase (LpxC). The state of the art of the design and investigation of inhibitors of bacterial metalloenzymes is presented, and challenges are outlined and discussed.
Keywords: UDP-3-O-acylglucosamine deacetylase